Development of a new mechanical electro hydraulic valvetrain system - Chung, Jongwon; Kim, Namho; Oh, Hyunjung; Choi, Myungsik; Kim, Wonkyu; Min, Kyoungdoug (Journal of mechanical science and technology, 2021)
Variable valve actuation (VVA) technologies can provide improvements in fuel economy of spark-ignition (SI) engines by shifting valve timings or generating valve profiles that can minimize pumping loss. Electro hydraulic valve (EHV) is one of VVA technologies that is highly flexible in producing valve profiles to control charge mass without throttle. In this work, a new EHV which has a unique operating mode, namely mechanical mode, is introduced. The mechanical mode enables operation of valvetrain under circumstances of EHV malfunctions: the mechanical electro-hydraulic valvetrain (MEHV) developed in this study was capable of stable operation under various operating modes at wide ranges of oil temperatures and cam speeds with appropriate valve seating velocity and ramp duration. The MEHV is a VVA technology that can resolve issues of previous EHVs which lacked reliability under emergency conditions.